Preeclampsia pathogenesis and prediction - where are we now: the focus on the role of galectins and miRNAs - Natasa Karadzov Orlic; Ivana Joksić (Hypertension in Pregnancy)
Preeclampsia is a complex, progressive multisystem hypertensive disorder during pregnancy that significantly contributes to increased maternal and perinatal morbidity and mortality. Two screening algorithms are in clinical use for detecting preeclampsia: first-trimester screening, which has been developed and validated for predicting early-onset preeclampsia but is less effective for late-onset disease; and the sFlt-1:PlGF biomarker ratio (soluble tyrosine kinase and placental growth factor) used in suspected cases of preeclampsia. This ratio has a high negative predictive value, allowing for the reliable exclusion of the disease. Both of these screening tests have not met expectations. This review attempts to summarize the current knowledge on the pathogenesis and prediction of preeclampsia and to draw attention to novel biomarkers with a focus on microRNAs and galectins. Although these molecules belong to two distinct biological classes, they functionally converge in regulating placental and immune pathways. Ample evidence supports their involvement in the molecular mechanisms underlying preeclampsia. Based on current knowledge, galectin-13, C19MC members, and miRNA-210 are associated with the trophoblast/placenta and conditions of placental ischemia or hypoxia. Their levels differ significantly in pregnant women at risk of preeclampsia as early as the late first and early second trimester, making them potential markers for predicting preeclampsia.